The Influence of Teachers' Strategies on The Process of Teaching the Portuguese Language by the Performance of Students in the 10th Grade at the Oriental General Secondary School Timor – Lorosa'e, Becora Dili, in the 2024 School Year - Conceição, Sancha Francisca da (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
In this research, the researcher examines a teacher's strategy is a set of techniques and procedures that he plans and implements the process of teaching the Portuguese language to achieve student performance. The specific objectives are as follows: to know the strategies of the teachers and the process of teaching the Portuguese language influence, simultaneously, the performance of the students in the 10th grade at the Escola Secundária Geral Oriental Timor – Lorosa'e, Becora Dili, in the 2024 school year. The data collection method used is the Qualitative and Quantitative method. The data collection technique is Entervista and Quistionaries. The result of the influence of the strategies of the teachers in the teaching process of the Portuguese language raise the performance of the students in the Escola Secundária Geral Oriental Timor – Lorosa'e (ESGORTIL) both individually and classically.